Dieng Culture Festival as a Reinforcement of Local Cultures in Globalization Era - Ervin Hidayat dan Ismi Dwi Astuti Nurhaeni (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
Dieng Culture Festival (DCF) is an event that offers a variety of traditional artsinitiated with performance of Kuda Lumping (leathered horse dance), RampakyasoDance, Wayang (shadow puppet), and finalized with dreadlock hair cuttingtraditional ceremony. Local wisdom in Dieng plateau is closely related to the localwisdom which is associated to God through a range of traditional ceremoniesavailable (Suyatno, 2011).The unique and varied cultures in Dieng certainly become pride and challenge thatmust be faced in order to maintain the cultures and inherit them for the nextgeneration. Thus, the rapid changes and development of this era also result inchanges on people’s life into a more modern way. Therefore, people tend to choosenew culture for it is considered more practical than the local one (Effendi, 2017).DCF aims the construction of new concept which is the acculturation of culture andnatural tourist destination. Its missions include the enhancement of economic levelof local people, preservation of Dieng cultures, and information spread about localcultures and customs in Dieng into broader community. This should be able todistribute the attractiveness in Dieng to potential visitors both local andinternational. Moreover, DCF is well-scheduled and published through any media(printed, sites, or social media). The event involves modern arts and music (Jazzand lantern festival) that attract more visitors to come (Diengnesia, 2017).Hence, this writing is descriptive analytics and discusses the purpose of DiengCulture Festival as an encouragement towards local or traditional cultures throughculture preservation as an effort to maintain Dieng’s identity in this rapiddevelopment in technology and modern world. The outcome of this researchincludes the description on how DCF could be an essential magnet to attract morevisitors so they can learn Dieng and its cultures deeply.Keywords: Dieng, Dieng Culture Festivals, local cultures, tourists